The Validity and Sensitivity of Rheumatoid Arthritis Pain Scale on a Different Ethnic Group From Indian Rheumatoid Arthritis Patients - Harpreet SINGH,; Sameer ARORA,; Vikram TANWAR,; Ankit KALRA,; Gagandeep SUKHIJA,; Nikhil GOVIL, (Archives of Rheumatology, 2020)
Objectives: This study aims to assess pain in rheumatoid arthritis (RA) patients by using Rheumatoid Arthritis Pain Scale (RAPS) and to find its correlation with Disease Activity Score 28 (DAS28) and Clinical Disease Activity Index (CDAI). Patients and methods: The study included 100 RA patients (23 males, 77 females; mean age 43.22 years; range, 19 to 72 years) who were subjected to RAPS questionnaire for pain assessment and DAS28 and CDAI for disease activity assessment. Spearman’s correlation coefficient was measured to assess the correlation of RAPS with DAS28 and CDAI. Cronbach’s alpha (α) was also measured for each scale to assess reliability. Results: The study group had a female to male ratio of 3.34:1. Mean values for RAPS, DAS28 and CDAI were 62.91, 5.59, and 25.24, respectively. RAPS was correlated with DAS28 and CDAI with correlation coefficients of 0.811 and 0.770, respectively. Cronbach’s α for RAPS, DAS28 and CDAI were 0.892, 0.814, and 0.833, respectively. Conclusion: Rheumatoid Arthritis Pain Scale had a strong positive correlation with disease activity measures of DAS28 and CDAI. RAPS also showed good correlation with core data set measures hence merits its place in clinical practice.